PENGARUH STRATEGI KOMUNIKASI DAN KUALITAS PELAYANAN UNIT TELLER TERHADAP KEPUASAN NASABAH PADA PT BNI TANJUNG BALAI KARIMUN KCP SEI LAKAM - Kasirul Fadhli Kasirul; Haryati Haryati (PROGRAM STUDI ILMU KOMUNIKASI, 2020)
PT Bank Negara Indonesia (BNI) Tanjung Balai Karimun branch is a state-owned company engaged in services and banking. This study aims to reveal: (1) The influence of PT BNI Branch Tanjung Teller Karimun KCP Sei Lakam communication strategy on customer satisfaction; (2) The Effect of PT BNI Tanjung Balai Karimun KCP Sei Lakam Teller Service Quality on customer satisfaction. The population in this study are deposit customers and cash withdrawals, from this population a sample of 30 people can be obtained in one week's collection. The technique used in this sample is Simple Random Sampling. Data collection instruments using a questionnaire that has been tested and has met the requirements of validity and reliability. The results of quantitative analysis using the equation of Multiple Linear Regression Analysis, with the design of hypothesis testing using the t test (Partial) and Test f (Simultaneous) with a significant level used is equal to 0.050 or 5%. The t test results showed that there was an influence between the communication strategy variable (X1) with t count (4,300)> t table (2,051) and Sig 0,000 <0.050 and the service quality variable (X2) with t count (2,300)> t table (2,051) and Sig 0.029 <0.050 to customer satisfaction at PT BNI Tanjung Balai Karimun KCP Sei Lakam. The results of the F test show that the Communication Strategy (X1) and Service Quality (X2) simultaneously influence the Customer Satisfaction (Y) of PT BNI Tanjung Karimun KCP Sei Lakam with a calculated F value (33,808)> F table (3,35) and sig 0,000 <0.050. Thus it can be concluded that in general the communication strategy and quality of Teller services significantly influence customer satisfaction of PT BNI Tanjung Karimun KCP Sei Lakam.